PHYTOCHEMICAL SCREENING AND TOXICITY TESTING OF MATURE SUGARCANE LEAF EXTRACT, SACCHARUM OFFICINARUM (LINNAEUS, 1753) - Rosales, Raamah C; Ramas, Cristina; Rosales, Maria Eden (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Sugarcane is an important agricultural crop in the Philippines. Massive volume of plant leaves is produced annually that can provide a considerable volume of samples for natural drug studies. This study aimed to determine the secondary compounds and biological effect of the mature sugarcane leaf extract. The phytochemical screening was conducted for the detection of secondary metabolites, namely: alkaloids, flavonoids, tannins, saponins, cardiac glycosides, carbohydrates and anthracene glycosides. Brine shrimp biological assay was used to determine the toxicity of the crude extract while LC 50 was utilized to analyze the toxicity of the different concentrations. The phytochemical screening positively detected the presence of the secondary metabolites except for saponins. The lethality assay on brine shrimp nauplii indicated high mortality on the highest concentration with no deaths recorded on the negative control using seawater. The LC 50 was determined at 34.06 that means 50% of the mortality rate occurred at this concentration. The LC50 has classified the 100 µL and 50 µL concentrations as extremely toxic while 10 µL, 1 µL, and 0.1µL concentrations were slightly toxic. Isolation and purification of the secondary metabolites may be conducted in the future to specify the compounds with its biological effects.